Necrosis-Induced Sterile Inflammation Mediated by Interleukin-1α in Retinal Pigment Epithelial Cells - Liu, Yang (PLoS One, 2015)
Endogenous danger signals released from necrotic cells contribute to retinal inflammation. We have now investigated the effects of necrotic cell extracts prepared from ARPE-19 human retinal pigment epithelial cells (ANCE) on the release of proinflammatory cytokines and chemokines by healthy ARPE-19 cells. ANCE were prepared by subjection of ARPE-19 cells to freeze-thaw cycles. The release of various cytokines and chemokines from ARPE-19 cells was measured with a multiplex assay system or enzyme-linked immunosorbent assays. The expression of interleukin (IL)–1α and the phosphorylation and degradation of the endogenous nuclear factor–κB (NF-κB) inhibitor IκB-α were examined by immunoblot analysis. Among the various cytokines and chemokines examined, we found that ANCE markedly stimulated the release of the proinflammatory cytokine IL-6 and the chemokines IL-8 and monocyte chemoattractant protein (MCP)–1 by ARPE-19 cells. ANCE-induced IL-6, IL-8, and MCP-1 release was inhibited by IL-1 receptor antagonist and by an IKK2 inhibitor (a blocker of NF-κB signaling) in a concentration-dependent manner, but was not affected by a pan-caspase inhibitor (Z-VAD-FMK). Recombinant IL-1α also induced the secretion of IL-6, IL-8, and MCP-1 from ARPE-19 cells, and IL-1α was detected in ANCE. Furthermore, ANCE induced the phosphorylation and degradation of IκB-α in ARPE-19 cells. Our findings thus suggest that IL-1α is an important danger signal that is released from necrotic retinal pigment epithelial cells and triggers proinflammatory cytokine and chemokine secretion from intact cells in a manner dependent on NF-κB signaling. IL-1α is therefore a potential therapeutic target for amelioration of sterile inflammation in the retina.